Going viral? Linking the etiology of human prostate cancer to the PCA3 long noncoding RNA and oncogenic viruses - Andre A Teixeira; Serena Marchiò; Emmanuel Dias‐Neto; Diana N Nunes; Israel T da Silva; Bryce Chackerian; Marc Barry; Richard C Lauer; Ricardo J Giordano; Richard L Sidman; Cosette M Wheeler; Webster K Cavenee; et al. (EMBO Molecular Medicine)
Graphical Abstract The hypothesis is discussed that prostate cancer marker lncRNA PCA3 was introduced into the human genome by an oncogenic virus, and that viral infection‐related mechanisms might underlie its overexpression and prostate cancer initiation and/or progression.